2021
DOI: 10.1002/ddr.21791
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐lipoic acid: A promising adjuvant for nonsteroidal anti‐inflammatory drugs therapy with improved efficacy and gastroprotection

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used in a wide variety of diseases due to their analgesic and anti-inflammatory effects, but their usage have been limited due to significant ulcerogenic side effects. In the present study, we aimed to evaluate the effect of α-lipoic acid (ALA) treatment on the anti-inflammatory activity of indomethacin (Indo) as well as the possible therapeutic effect of ALA on high dose Indo-induced gastropathy in female mice. Mice were treated with Indo (5 or 30 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In addition, ALA reversed MTXinduced inflammatory hints because it notably reduced the level of TNF-α, which is consistent with the earlier stated antioxidant/anti-inflammatory effects of ALA. [20] Other studies have also shown that ALA has anti-inflammatory effect by decreasing the level of TNF-α. [41,42] Furthermore, ALA reversed MTX-induced ROS-mediated damage, inflammation, and disruption in the testis as evidenced by decreasing iNOS and TNF-α immunoreactivity and histopathological improvement compared with MTX alone, which is in agreement with prior studies. [20] Here, we showed that the ALA-treated decline in NO levels was attributable to downregulation of iNOS expressions in the testis.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, ALA reversed MTXinduced inflammatory hints because it notably reduced the level of TNF-α, which is consistent with the earlier stated antioxidant/anti-inflammatory effects of ALA. [20] Other studies have also shown that ALA has anti-inflammatory effect by decreasing the level of TNF-α. [41,42] Furthermore, ALA reversed MTX-induced ROS-mediated damage, inflammation, and disruption in the testis as evidenced by decreasing iNOS and TNF-α immunoreactivity and histopathological improvement compared with MTX alone, which is in agreement with prior studies. [20] Here, we showed that the ALA-treated decline in NO levels was attributable to downregulation of iNOS expressions in the testis.…”
Section: Discussionsupporting
confidence: 90%
“…Originally, this organosulphur compound is located in the mitochondria and acts as a cofactor for pyruvate dehydrogenase/α‐ketoglutarate dehydrogenase complexes in the biological system. Recent studies have been focused on its therapeutical potentials such as nephroprotective, [2] anti‐inflammatory, [3] anti‐apoptotic, [4] and neuroprotective [5] properties. Interestingly, several clinical studies have suggested a promising ameliorative potential of α‐LA against liver diseases by improving serum adiponectin and IL‐6 levels [6] and reducing tissue oxidative damage and hypoxia [7] .…”
Section: Introductionmentioning
confidence: 99%
“…However, NSAIDs have various adverse effects on the gastrointestinal tract, liver, nervous, urinary tract, blood, and cardiovascular system, especially those occurring in the stomach. These effects can lead to issues, such as gastric mucosal erosion, ulcer, hemorrhage, and perforation [ 2 ]. In recent decades, with the increasing clinical application range and dosage, the incidence rate of NSAIDs-related gastric ulcer is also on the rise [ 3 ].…”
Section: Introductionmentioning
confidence: 99%